Albatross-Cephalopod interactions in Antarctic Ocean: implications for albatross ecology and conservation - Alvito, Pedro Miguel Oliveira Soromenho de, 1989- (2012)
Tese de mestrado. Biologia (Biologia da Conservação). Universidade de Lisboa, Faculdade de Ciências, 2012 Albatrosses can be used as biological sampling tools to investigate poorly known organisms, such as the Southern Ocean cephalopods. The aims of the present study were to characterize the albatrosses diet, with relevance to the cephalopod component, during the reproductive period of wandering (Diomedea exulans), black-browed (Thalassarche melanophrys) and grey-headed (Thalassarche chrysostoma) at Bird Island (South Georgia), and at the end of inter-breeding/beginning of breeding period (EIB/BB) of the last two albatross species, to assess the habitat and trophic level of key cephalopods species by stable isotopes analyses, to compare both sampled periods, to identify threats and suggest measures to reinforce these albatrosses conservation. During the reproductive period, black-browed albatross fed mainly on fish, the grey-headed albatross on cephalopods, and the wandering albatross on both prey. The four main cephalopod species found in the albatrosses diets were Kondakovia longimana, Martialia hyadesi, Moroteuthis knipovitchi and Galiteuthis glacialis during the reproductive period. For the first time, black-browed and grey-headed albatrosses diets during the EIB/BB period were analyzed. K. longimana was reported as the main cephalopod species during this period and it was found that scavenging could play an important role in albatrosses diet. Based on the stable isotopic signatures of the cephalopod lower beaks, the main species were from Antarctic and sub-Antarctic waters and could be grouped in four trophic levels. The main threats to albatrosses included: i) interaction with fisheries, ii) the possible lower availability of krill in South Georgia region during the reproductive period, and iii) the almost absence of the M. hyadesi in grey-headed albatrosses diet. Some measures to reinforce the conservation of the three studied albatross species are related to the fishery and krill industries and by a ...